Treatment of HCV infection with direct-acting antiviral agents. Real life experiences from the Euro-Asian region - Örmeci, Necati; Gülşen, Murat Taner; Sezgin, Orhan; Aghayeva, Sevda; Demir, Mehmet; Köksal, Iftihar; Güner, Rahmet; Erarslan, Elife; Asiller, Özgün Ömer; Balkan, Ayhan; et al. (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Hepatitis C virus (HCV) infection is a common disease that causes liver cirrhosis, hepatocellular carcinoma, and extra hepatic manifestations with high mortality and morbidity rates. This study aimed to present real-life experiences and results of treatment of HCV infection with direct-acting antiviral agents (DAAs) from the Euro-Asian region, including Turkey and Azerbaijan. Materials and Methods: A total of 1224 patients with chronic HCV infection were treated with DAAs in accordance with the international guidelines for the management of HCV infection. The mean age was 58.74±14.75 years, with 713 (58.25%) females. The genotypes of the patients were as follows: genotype 1b, 83.36% (n=1024); genotype 1a, 8.08% (n=99); genotype 2, 2.85% (n=35); genotype 3, 3.34% (n=41); genotype 4, 1.71% (n=21); and combined genotypes, 0.32% (n=4). Approximately 808 patients were treated with sofosbuvir-based DAAs with or without Ribavirin for 12 or 24 weeks, whereas 416 patients were treated with the Paritaprevir, Ombitasvir, Ritonavir.Dasabuvir (PROD) regimen with or without Ribavirin for 12 weeks or 24 weeks. Results: At the end of follow-up examinations, 1183 patients (97.93%) had sustained virological response (SVR), 17 (1.40%) died of reasons unrelated to the treatment regimen, 12 had recurrence after treatment, and 129 (10.67%) had adverse events like anemia, itching, and weakness. Conclusion: In this large cohort of HCV-infected patients, treatment with DAAs yielded a high overall SVR rate of 97.93%. DAAs were safe and well-tolerated. Thus, the elimination of HCV infection is no longer a dream worldwide.